Dzieci jako adresaci i odbiorcy reklam telewizyjnych - Starosta, Anna Maria (Kultura-Społeczeństwo-Edukacja, 2012)
Living in XXI century, experiencing personally technological and psycho – social changes that modern world provides us with, usually we cannot see many phenomena. One of them is undoubtedly the impact of TV commercials on children’s personality development process. – Yet, it has become one of the most important factors affecting the child in the process of the social – economic development that exerts great influence on the way of thinking and behavior. It mainly results from the fact that children today live in a world completely different from previous generations to such an extent that more and more often their childhood is described as „television childhood”. The child starts to experience the television (and what comes with it – TV commercials) at home continues throughout the childhood and his youth. A particular concern is the fact that children nowadays have a contact with the medium very early – it starts once their level of development allows them to focus on the screen for some (not long though) time. The range of their contact with the small screen is very wide – what is the most important – it is systematic, daily, lasting for many hours, it has the multifaceted nature and individual character.